2013
DOI: 10.1186/1476-069x-12-90
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between adolescents’ well-being and their wireless phone use: a cross-sectional study

Abstract: BackgroundThe exposure of young people to radiofrequency electromagnetic fields (RF-EMFs) has increased rapidly in recent years with their increased use of cellphones and use of cordless phones and WiFi. We sought to ascertain associations between New Zealand early-adolescents’ subjective well-being and self-reported use of, or exposure to, wireless telephone and internet technology.MethodsIn this cross-sectional survey, participants completed questionnaires in class about their cellphone and cordless phone us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(91 citation statements)
references
References 23 publications
(24 reference statements)
7
80
0
4
Order By: Relevance
“…Our results of the cross-sectional analyses, where we found an increase in self-reported health symptom reports in relation to various self-reported usage measures, are in line with other cross-sectional studies on symptoms, mental health or sleeping problems (Byun et al 2013;Ikeda et al 2014;Koivusilta et al 2007;Redmayne et al 2013;Roser et al 2016a;Schoeni et al 2015b;Soderqvist et al 2008). …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our results of the cross-sectional analyses, where we found an increase in self-reported health symptom reports in relation to various self-reported usage measures, are in line with other cross-sectional studies on symptoms, mental health or sleeping problems (Byun et al 2013;Ikeda et al 2014;Koivusilta et al 2007;Redmayne et al 2013;Roser et al 2016a;Schoeni et al 2015b;Soderqvist et al 2008). …”
Section: Discussionsupporting
confidence: 75%
“…In a large Swedish cross-sectional study of 2000 adolescents, selfreported use of mobile phones was related to self-reported health complaints such as tiredness, stress, headache, anxiety, concentration difficulties and sleep disturbances (Soderqvist et al 2008). Redmayne et al (2013) found significant cross-sectional associations between adolescents' well-being and their wireless phone use, with most consistent associations for headache. In a cross-sectional Korean study, feeling of discomfort and dry skin were associated with the number of outgoing calls per day and dry skin, fatigue and dizziness were associated with average duration per call (Byun et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, storage location varied considerably between beach and city areas in coastal USA, and in some areas of India women rarely carried a handbag and therefore more often used a trouser pocket. More recently, students aged 10 to 13 years reported most commonly storing their phone in the front/side pocket of a skirt or trousers [13]. In that study, 3 (< 2% of girls) reported keeping it tucked in the bra and a further 3 hung it round the neck against the chest, both locations being self-nominated in the ‘other’ category.…”
Section: Introductionmentioning
confidence: 99%
“…However, this was not done so far, although impaired well-being (Byun et al 2013a;Redmayne et al 2013) and Attention Deficit Hyperactivity Disorder (ADHD) symptoms (Byun et al 2013b) were linked to amount of mobile phone use in children and adolescents. Thus, it remains unclear, if these adverse effects in adolescents may be attributed to problematic use of the mobile phone or amount of mobile phone use.…”
Section: Introductionmentioning
confidence: 99%